Magnetic Resonance Angiography of the Hand Vasculature in Patients With Systemic Sclerosis and Systemic Lupus Erythematosus. (June 2023) - Asadourian, Paul A.; Chen, Aaron Z.; Aristega Almeida, Bryan; Gordon, Jessica K.; Burge, Alissa J.; Fufa, Duretti T.
Background: When patients with systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) develop digital ischemia, conventional angiography (CA) is traditionally used to assess hand vasculature. Recently, Chang et al described an angiographic classification system for patients with SSc. Conventional angiography uses intravascular contrast agents that are nephrotoxic and vasoconstrictive. Owing to these limitations, this study assesses the use of contrast-enhanced magnetic resonance angiography (MRA) as an alternative to CA to evaluate hand vasculature in patients with digital ischemia. Methods: This retrospective case series reports on 38 contrast-enhanced MRAs of hand vasculature from 30 symptomatic patients with SSc (N = 21) or SLE (N = 9). The radial and ulnar arteries (RA, UA) and the superficial and deep palmar arches were evaluated at standard reference points both quantitatively and qualitatively for their diameter, patency, and Chang classification. Results: In SSc MRAs (n = 26), the UA was significantly smaller than the RA and was occluded in 46%. In SLE MRAs (n = 12), the UA and RA had no difference in diameter and the UA was occluded in 25%. In SSc, the most common Chang classification was type 2 (UA involvement) in 44%. In SLE, the most common Chang classification was type 4 (UA and RA involvement) in 45%, with 18% classified as type 2. Conclusions: Contrast-enhanced MRA used to assess hand vasculature in SSc patients with digital ischemia shows similar patterns of vascular involvement as previously demonstrated by CA. While vascular involvement in SSc predominantly involves the UA, the RA is also frequently involved in SLE.